Guy De Maupassant’s Use of Phraseological Units in His Works (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the use of phraseological units in the literary works of Guy de Maupassant. Phraseological units—including idioms, set expressions, and colloquial phrases—play a significant role in Maupassant’s realistic storytelling style. By analyzing selected examples from his short stories, the study explores how these expressions contribute to characterization, dialogue authenticity, and stylistic richness. Furthermore, the article touches on the challenges of translating Maupassant’s phraseological expressions into English, emphasizing the cultural nuances embedded in his language. The findings highlight the importance of phraseology in enhancing literary meaning and reader engagement.